2021
DOI: 10.1088/1402-4896/ac2658
|View full text |Cite
|
Sign up to set email alerts
|

A new weighted version of alpha power transformation method: properties and applications to COVID-19 and software reliability data

Abstract: This paper is an effort to propose a new method to generate probability distributions based on alpha power transformation method for more flexibility. We refer to the new method as modified alpha power transformed method. The new proposed method can be considered as a weighted version of the alpha power transformation method with more ability to model various types of data. A special case has been studied in detail namely; one parameter exponential distribution. The new generalization of the traditional expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…where α and θ are the shape parameters while λ is the scale parameter. It is observed that F(x; α, λ, 1) reduces to the MAPTE by [18], F(x; → 1, λ, 1) tends to the exponential distribution, F(x; → 1, λ, 2) tends to the Rayleigh distribution, F(x; α, λ, 2) tends to the MAPT Rayleigh distribution and F(x; → 1, λ, θ) tends to the Weibull distribution. It is to mentioned hare that the MAPTW distribution can be considered as a weighted version of the APW distribution with weight function 1 + α − α 1−e −λx θ −2 .…”
Section: The Modified Alpha Power Transformed Weibull Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…where α and θ are the shape parameters while λ is the scale parameter. It is observed that F(x; α, λ, 1) reduces to the MAPTE by [18], F(x; → 1, λ, 1) tends to the exponential distribution, F(x; → 1, λ, 2) tends to the Rayleigh distribution, F(x; α, λ, 2) tends to the MAPT Rayleigh distribution and F(x; → 1, λ, θ) tends to the Weibull distribution. It is to mentioned hare that the MAPTW distribution can be considered as a weighted version of the APW distribution with weight function 1 + α − α 1−e −λx θ −2 .…”
Section: The Modified Alpha Power Transformed Weibull Distributionmentioning
confidence: 99%
“…For example, alpha power Weibull distribution by [8], alpha power generalized exponential by [15], alpha power transformed inverse Lindley distribution by [16] and alpha power Gompertz distribution by [17]. To add more flexibility to the APT method, Alotaibi et al [18] proposed a new form of the APT method which is called the modified APT (MAPT) method. The CDF and the PDF of the MAPT method are, respectively, given by…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Johnson et al [17] for further information on the IW distribution. In this study, we offer a new three-parameter IW distribution utilizing the same idea proposed by Alotaibi et al [18]. The modified alpha power transformed IW (MAPTIW) distribution is the name given to the new distribution.…”
mentioning
confidence: 99%
“…It includes some lifetime distributions, such as IW, inverted exponential and inverse Rayleigh distributions. Recently, The alpha power transformation approach was used by Alotaibi et al [18] to suggest a new method for adding a new shape parameter to a baseline distribution. Modified alpha power transformation (MAPT) was the name given to the approach they proposed.…”
mentioning
confidence: 99%